Atomic‐Level Fe‐N‐C Coupled with Fe3C‐Fe Nanocomposites in Carbon Matrixes as High‐Efficiency Bifunctional Oxygen Catalysts. Issue 6 (29th December 2019) - Sun, Xueping; Wei, Peng; Gu, Songqi; Zhang, Jinxu; Jiang, Zheng; Wan, Jing; Chen, Zhaoyang; Huang, Li; Xu, Yue; Fang, Chun; Li, Qing; Han, Jiantao; et al.
Abstract: Highly active and durable bifunctional oxygen electrocatalysts are of pivotal importance for clean and renewable energy conversion devices, but the lack of earth‐abundant electrocatalysts to improve the intrinsic sluggish kinetic process of oxygen reduction/evolution reactions (ORR/OER) is still a challenge. Fe‐N‐C catalysts with abundant natural merits are considered as promising alternatives to noble‐based catalysts, yet further improvements are urgently needed because of their poor stability and unclear catalytic mechanism. Here, an atomic‐level Fe‐N‐C electrocatalyst coupled with low crystalline Fe3 C‐Fe nanocomposite in 3D carbon matrix (Fe‐SAs/Fe3 C‐Fe@NC) is fabricated by a facile and scalable method. Versus atomically FeN x species and crystallized Fe3 C‐Fe nanoparticles, Fe‐SAs/Fe3 C‐Fe@NC catalyst, abundant in vertical branched carbon nanotubes decorated on intertwined carbon nanofibers, exhibits high electrocatalytic activities and excellent stabilities both in ORR ( E 1/2, 0.927 V) and OER ( E J=10, 1.57 V). This performance benefits from the strong synergistic effects of multicomponents and the unique structural advantages. In‐depth X‐ray absorption fine structure analysis and density functional theory calculation further demonstrate that more extra charges derived from modified Fe clusters decisively promote the ORR/OER performance for atomically FeN4 configurations by enhanced oxygen adsorption energy. These insightful findings inspire new perspectives for the rational design and synthesis of economical–practical bifunctional oxygen electrocatalysts. Abstract : The atomically dispersed FeN4 configurations modulated by appropriate low crystalline Fe3 C‐Fe species can dramatically boost the oxygen reduction reaction/oxygen evolution reaction performance as the moderate electronic regulation. This finding not only clarifies the essential factor for the active site of Fe‐N‐C catalysts, but also inspires a new avenue for engineering efficient and economical bifunctional oxygen catalysts.